SURG-32. DIFFERENCES IN SURGICAL OUTCOME BETWEEN VON HIPPEL-LINDAU DISEASE RELATED AND SPORADIC HEMANGIOBLASTOMAS IN THE CENTRAL NERVOUS SYSTEM. (9th November 2020) - Nambu, Shohei; Takayanagi, Shunsaku; Takami, Hirokazu; Kin, Taichi; Tanaka, Shota; Nakatomi, Hirofumi; Saito, Nobuhito
Abstract: Central nervous system hemangioblastoma (CNS HB) is a benign but highly vascular tumor, which accounts for 1.7% of all intracranial tumors. CNS HBs predominantly arise in the cerebellum, brainstem, and spinal cord. Approximately 20% of CNS HB is related to von-Hippel-Lindau (VHL) disease and repeated surgical resections are often required in VHL patients due to the presence of multiple CNS HBs. To explore the differences of surgical effect between VHL disease related and sporadic CNS HBs, outcome analyses were performed based on the tumor locations. PATIENT AND METHODS: A total 83 cases that underwent surgical resections of CNS HBs at Tokyo University in 1996-2019 were included. Clinical information including age, sex, number of past surgical resections, pre- and post-operative modified Rankin Scale(mRS) were examined. RESULTS: Regarding the etiology, 46 VHL cases(cerebellum:30, medulla oblongata:6, spinal cord:10) and 37 sporadic cases (cerebellum: 28, medulla oblongata:4, spinal cord:5) were enrolled. The average changes in the postoperative mRS minus preoperative mRS were cerebellum -0.9/medulla oblongata -0.5/spinal cord -0.8 for VHL cases, and cerebellum -0.75/medulla oblongata -1/spinal cord -1 for sporadic cases. Fisher`s exact tests were used for between-group comparison. DISCUSSION: The study showed no statistically significant difference between cerebellar and spinal cord cases regarding the perioperative change in the patient capability. Because of multiple lesions and repeated surgeries, VHL patients have a possibility to present with worse neurology after surgery. Further analysis is needed to clarify differences in surgical outcome for VHL disease related and sporadic related CNS HBs.